Effect of number of axillary buds on stem cuttings of sweet potato (pomoea batatas) CV. 'Blesbok' productivity using sack gardening technology - Moitsi, Lebogang Rejoice (My University, 2022)
Worldwide, water scarcity, land degradation and unavailability of agricultural lands have posed serious threats on food security and income generation. Hunger, micronutrient deficiencies and starvation are likely to go up in Africa due to increasing urbanisation and rise in global food prices. As a result, it is important to identify innovative vegetable growing-based strategies, which can increase access to food by utilising the limited space available in rural and urban areas. Therefore, sack gardening technology could be a solution to both the lack of arable land and water scarcity in urban and rural areas. The objective of the study was to determine whether axillary bud number will have an effect on agronomic parameters and yield of sweet potato cv. 'Blesbok' produced using the sack gardening technology. Treatments, namely, 1, 2, 3, 4, and 5 number of axillary buds per stem cutting, were arranged in randomised complete block design, with 10 replicates. One bud (1) was used as a control. Different stem cuttings measuring from 10 to 30 cm long with approximately one (1) to six (6) axillary buds were collected from mature sweet potato plantation at a certified nursery from cv. 'Blesbok'. A total of eight (8) stem cuttings were planted in sacks consisting of growing media mixture of steam pasteurised loam soil and compost (3:1 v/v), 4 on top side of the sack and the remaining four on the side-holes of the sack. Insect pests were scouted and monitored weekly, while diseases were managed using spraying programmes as in commercial sweet potato production systems. Two weeks after transplanting, each plant was fertilised with 5 g nitrogen (N), phosphorus (P), and potassium (K) 2:3:2 (26) + 0.5% Zinc (Zn) + 5% sulphur (S) and 5% calcium (Ca). Number of axillary buds had significant effects on vine length, fresh shoot mass, number of shoots and dry shoot mass contributing 59%, 58%, 45% and 58% in total treatment variation (TTV), respectively, whereas axillary bud numbers had no significant effects on fresh tuberous root mass, chlorophyll content, vine stem diameter, tuberous root diameter, tuberous root length, dry tuberous root mass and number of tuberous roots. Relative to control (one bud), two (2), three (3), four (4), five (5) number of axillary buds decreased vine length, fresh shoot mass and dry shoot mass by 8-37, 30-55 and 26-55%, respectively. However, relative to control (one bud), number of axillary buds increased number of shoots by 8-17%. The quadratic relationship models were explained by 95, 92, 96 and 98% of vine length (VL), number of shoots (NS), fresh shoot mass (FSM) and dry shoot mass (DSM), respectively. In conclusion, findings of the study demonstrated that a single (1) or two (2) axillary bud(s) on stem cuttings of sweet potato CV. „Blesbok‟ showed better results for both yield and growth parameters as compared to three (3), four (4) and five (5) buds.
Thesis (M.Sc. (Horticulture)) --University of Limpopo, 2022
Keywords: Axillary bud; Gardening technology; Treatment; Sweet potato; Sack gardening technology; Sweet potatoes -- Breeding; Sweet potatoes -- Planting; Buds; Food security